Disparitas Penuntutan Tindak Pidana Kepabeanan: Studi Putusan Nomor 42/Pid.B/2024/PN Rhl dan Putusan Nomor 43/Pid.B/2024/PN Rhl - Hardiansyah, Ricki; Siregar, Muhammad Yusuf; Tampubolon, Wahyu Simon (SIGn Jurnal Hukum, 2024)
This research aims to analyze the disparity in the charges of customs crimes in a case study of Decision Number 42/Pid.B/2024/PN Rhl and Decision Number 43/Pid.B/2024/PN Rhl. This normative legal research employs a tripartite approach, encompassing a statute approach, a comparative approach, and a case study approach. Data analysis uses a qualitative content analysis approach to describe the problems and address the research objectives. The research results indicate a significant disparity in the charges between the two decisions, while both defendants were proven to have jointly committed acts that fulfil the elements of a criminal offence as regulated and punishable under Article 102 point an of Law Number 17 of 2006 Juncto Article 55 section (1) of the Penal Code. Conversely, the Public Prosecutor presented substantially different charges: two years imprisonment for one defendant and four years for the other defendant. This disparity in the charges, which reached twice as much, raises serious issues regarding proportionality and fairness, violates the principle of equality before the law, negatively impacts legal certainty (rechtszekerheid), which in turn can erode public trust in the judicial system and hinder fair law enforcement. To mitigate the disparity in the charges, comprehensive and systemic efforts are needed, including the establishment of detailed and structured sentencing guidelines, increasing the capacity and professionalism of Public Prosecutors, strengthening oversight and evaluation mechanisms of the Public Prosecutor’s performance, and implementing an effective case management system to identify potential disparities early on.